Energy Efficient Homes: The Irrigation System - Melissa B. Haley; Michael D. Dukes; Stacia Davis; Mary Shedd; Bernard Cardenas-Lailhacar (EDIS)
FCS-3274, a 10-page illustrated fact sheet by Melissa B. Haley, Michael D. Dukes, Stacia Davis, Mary Shedd, and Bernard Cardenas-Lailhacar, describes strategies and technologies for efficiency in home lawn irrigation systems. Includes references. One of an Energy Efficient Homes series. Published by the UF Department of Family Youth and Community Sciences, June 2008.